The level of knowledge of the skills of teaching reading comprehension based on effective instruction for teachers of learning disabilities in Jeddah - Mobajar, Wafa Yahia; Gharib, Reem Mahmoud (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to reveal the level of knowledge of reading comprehension teaching skills based on effective instruction for learning disabilities teachers in Jeddah. The descriptive curriculum was used, and the reading comprehension teaching skills test based on effective instruction was prepared by the two researchers to achieve the goal of the study. It was applied to a simple random sample of 53 teachers of learning disabilities in Jeddah. The results showed that the level of possession of learning disabilities teachers of the skills of teaching reading comprehension based on effective instruction was (40.83%), which is a low degree. Based on that result, the study recommended the development and organization of training programs and courses aimed at preparing teachers of students with learning disabilities in light of the modern trends of the Ministry of Education, which include focusing on developing reading comprehension skills of students, and work to develop guides for teachers of students with learning disabilities by the competent authorities that include the most important strategies for teaching reading comprehension and procedures for their application in accordance with the principles of effective instruction and to support them with applied models, and work to update them constantly.